Consumer Interaction, Perception, and Decision: An Observational Study of Visitor Behavioral at Kopi Luwak Cikole: Interaksi, Persepsi, dan Keputusan Konsumen: Studi Observasi Perilaku Pengunjung di Kopi Luwak Cikole - Cindy Berliana Febriyanti; Chintya Sari Monica Putri; Inggrit Putri Admadaraja Admadaraja; Nadine Marsha Zerlinda; Tofan Tri Nugroho (Procedia of Social Sciences and Humanities, 2026)
This study aims to analyze the impact of interactions and consumer perceptions on the purchasing decisions of visitors at Kopi Luwak Cikole, Bandung. The background of this research is due to the growing trend of coffee tourism and changes in people's lifestyles that make cafes a place for social gatherings as well as a recreational facility. The methodology used was a descriptive qualitative approach through direct observation, short interviews, and documentation. Research findings indicate that the way visitors interact with each other, communicate with staff, and engage on social media can contribute to a better shopping experience. Consumers' perceptions regarding the natural environment, the service provided, the taste offered, and the available facilities also influence their desire to buy coffee and revisit. Visitors not only evaluate the quality of the products, but also pay attention to the emotional experience as well as the comfort at the place. The combination of social interaction and positive perceptions has been proven to strengthen purchasing decisions. This study is expected to serve as a reference for café managers in improving services and marketing strategies that focus on consumer experience. Highlights: Active communication among visitors and staff generates positive emotional shopping experiences. Favorable evaluations of natural environments and educational facilities dictate buying choices. Integrated recreational concepts foster higher patron loyalty and subsequent revisit intentions. Keywords: Behavioral Dynamics, Emotional Engagement, Educational Facilities, Destination Management, Revisit Intentions